Current approaches to the digital product passport for a circular economy: An overview of projects and initiatives - Maike Jansen; Bastian Gerstenberger; Jan Bitter-Krahe; Holger Berg; János Sebestyén; Jonas Schneider (Wuppertal Institut für Klima, Umwelt, Energie, 2022)
A large number and variety of activities are being undertaken to introduce Digital Product Passports (DPPs). However, only a few DPPs have made it into practice so far, so there is some uncertainty about which impact DPPs will actually have. With this paper, we aim to provide a structured overview of the current development of DPPs. We provide insights of 76 current corporate, policy, and research activities that exist and their objectives. To allow for a structured assessment and discussion of the diverse approaches we defined 13 criteria for a comparable description, categorization and evaluation. We expect that this overview will not only encourage feedback and contributions from the DPP community, as well as valuable discussions with and among experts. It is also intended to help promote and facilitate the adoption of DPPs for the Circular Economy by facilitating collaborations and suggestions for ongoing activities.
urn:nbn:de:bsz:wup4-opus-80426
Keywords: 330